Volumen de residuos de la construcción generados en la ciudad de Riobamba - l Bravo Zúñiga, Santiago Israe (2018)
The construction as a core of Economic Globalization is one of the most productive sectors worldwide, the greatest demand for materials handled by this sector has generated alarming aspects such as: the constant generation of large volumes of waste resulting from the construction of new works, demolition and remodeling of old works and their inadequate final disposal, which generates environmental and social problems. At the global level, the volume of waste produced by the construction sector is a subject for which specific stadistics do not exist; Riobamba town does not have statistical information regarding the volume production of waste located in illegal dumps as well as in a controlled way in the general landfill CGIDS (Integrated Solid Waste Management Center) enabled by the municipality of the city, whose information show the real state of the problem that brings this type of waste. The main objective of this research work is to determine the volume generation of construction waste. For which direct field measurements were made of the weekly discharges of waste located in illegal dumps through topographic surveys considering drone photogrammetry as an ideal and suitable method for this type of measurements, as well as the recording of the waste that entered the CGIDS in a controlled manner. The results of this study indicated that in Riobamba a total volume of construction waste was generated equal to 4,112.73 m3 (3,416.04tn) during of 8 weeks of sampling. A 29% of these are appropriately arranged in the CGIDS, while the remaining 71% is illegally and uncontrolled deposited.